2004
DOI: 10.1051/apido:2004028
|View full text |Cite
|
Sign up to set email alerts
|

Queen honey bee introduction and early survival ? effects of queen age at introduction

Abstract: -The survival of honey bee Apis mellifera queens to 14 days and 15 weeks after introduction into an established bee colony increases with increasing age of the queen at introduction. Survival rates increased strongly to high levels for queen bees introduced between 7 and 24 days of age and at a slower rate for queens introduced at ages up to 35 days. The survival rates were similar for sister queens introduced into two unrelated apiaries suggesting that apiary site and beekeeper management differences had mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 4 publications
2
17
0
2
Order By: Relevance
“…In another study, Rhodes et al (2004) reported that young NMQs allowed to lay for several weeks in nucleus colonies before introduction into large colonies had lower supersedure and higher survival rates, compared to queens that were caged and forced to reabsorb eggs during transport soon after the start of egg laying. Free et al (1992) reported that workers bees pay more attention to queens that have been mated for two months or more.…”
Section: Pheromone Development and Queen Acceptancementioning
confidence: 99%
“…In another study, Rhodes et al (2004) reported that young NMQs allowed to lay for several weeks in nucleus colonies before introduction into large colonies had lower supersedure and higher survival rates, compared to queens that were caged and forced to reabsorb eggs during transport soon after the start of egg laying. Free et al (1992) reported that workers bees pay more attention to queens that have been mated for two months or more.…”
Section: Pheromone Development and Queen Acceptancementioning
confidence: 99%
“…For these reasons, beekeepers claim that mated queens purchased from registered queen breeders were small and of low quality because of their low fecundity, poor survival, and weak colonies. Queen quality can be assessed using a variety of fitness-related criteria such as live weight, ovariole number, spermathecae size, and mating success (number of spermatozoa in the spermatheca) (Zhdanova, 1967;Woyke, 1971;Rhodes et al, 2004). The aim of this study is to assess queen quality based on such queen reproductive traits as live weight, spermathecal volume, number of spermatozoa, and number of ovarioles.…”
Section: Gregorc and Smodiš šKerlmentioning
confidence: 99%
“…Teknik arıcılıkta, ana arıyı kontrollü bir şekilde yetiştirmenin önemli olduğu kadar, bu ana arıları yeni kolonilere kabul ettirmek de önemlidir. Genç yumurtlayan ana arıların yeni koloniye kabulünde; ana arı tarafından [44] salgılanan feromonların etkili olduğu bildirilmiştir ( [3], [8], [10], [56]- [59] ). Bu çalışmada Ege, Kafkas ve farklı zamanlarda araştırma ve yetiştirme amacıyla ülkeye getirilen İtalyan ırklarına mandibular bez feromonlarına ilişkin bilgiler üretilmiş ve ileride yapılacak çalışmalara temel oluşturmuştur.…”
Section: Bulgular (Results)unclassified